Stunting as a Risk Factor for Dental Malocclusion in Children Aged 34-59 Months - Day, Nora Fitri; Hidayat, Melania; Zahara, Meutia; Abdullah, Asnawi (Jurnal Penelitian Kesehatan SUARA FORIKES, 2025)
The impacts of stunting are not only reflected in reduced height but can also lead to diminished learning abilities and cognitive development, as well as an increased risk of chronic diseases later in life. This study aimed to analyze the relationship between stunting and the risk of dental malocclusion in Pidie District. This study used a cross-sectional design and conducted in 10 health care centres in Pidie district. A total of 108 children was selected as a sample using an accidental sampling method. Data analysis was carried out in bivariate and multivariate analysis using Chi-square and logistic regression tests. This research found that 24,07% of children aged 34-59 months in Pidie were stunting. The stunted children have a risk of 1086,48 times higher to experience malocclusion than non-stunted children after controlling variables mother and father occlusion. As conclusion, stunting affects the occurrence of malocclusion. Therefore, comprehensive education about malocclusion issues and it impacts is required.Keywords: stunting; dental malocclusion; cross-sectional study; child health